A retrospective review of risk factors for recalcitrant peptic structures - Ndlebe, Babalwa (Division of General Surgery, 2026)
Introduction: Peptic strictures (PS) are a common benign cause of dysphagia, but a scarcity of local data is available as regards identifying risk factors associated with recalcitrancy. Methods: Single centre retrospective audit of PS undergoing endoscopic management between 1st March 2018 and 1st March 2022, aiming to identify recalcitrancy risk factors. Results: Of 69 patients (37 male, 53.4%) with PS, 27 (39.1%) were diagnosed with recalcitrant strictures. Most strictures were positioned distally (53; 76.8%) with an associated hiatus hernia in 52 (75.4%). While comorbidities were not associated with recalcitrancy, younger age was a risk factor (recalcitrant stricture group median age 51 (IQR 38.5-61.0 years) versus non-recalcitrant group median age 62.5 (IQR 48.5-70.8 years); p=0.044). Although HIV status did not affect recalcitrancy risk, taking oral antiretrovirals (ARVs) was significantly associated with PS recalcitrancy (p=0.032; OR 4.55). Presenting degree of dysphagia (p<0.001; OR 16), requiring more than 3 dilatations (p<0.001), and smaller index residual oesophageal lumen (p<0.001) were all significantly associated with stricture recalcitrancy. Fourteen patients were temporarily stented (having a total of 24 stents placed). Thirteen patients had post endoscopic complications with most of these complications occurring amongst the recalcitrant group (n=11). Four complications occurred during endoscopy, two partial thickness tears managed endoscopically, a gastric perforation requiring an over-the-scope-clip closure and one sedation related hypoxia requiring a short period of bag-mask-valve ventilation and sedation-reversal. Two deaths occurred in the cohort; one from a suspected aspiration pneumonia five days after last dilatation and one from a suspected missed oesophageal perforation (2.3% immediate endoscopic intervention complication rate for 265 dilatations performed). Conclusion: Locally pill oesophagitis related to ARVs has been identified as a potential cause of recalcitrancy; identifying at-risk patients early may allow for management adjustments to improve outcomes.